La nueva participación ciudadana en Ecuador y Bolivia ¿Resultados de la lucha del movimiento indígena-campesino? - Colpari, Otto (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The Andean countries of Ecuador and Bolivia have begun a new political process with the implementation of citizen participation wich is found in the current constitution and related laws. This process is the product of the mobilization of various social sectors, particulary the indigenous-peasant movement. Therefore, this article attempts to analyze the main elements of citizen participation, its legal context and the outcome of political projects such as state modernization and New Public Management.
Keywords: citizen participation; modernity; mechanisms of participation